2013
DOI: 10.1111/1462-2920.12285
|View full text |Cite
|
Sign up to set email alerts
|

Gastric microbiota is altered in oesophagitis and Barrett's oesophagus and further modified by proton pump inhibitors

Abstract: Gastro-oesophageal reflux can cause inflammation, metaplasia, dysplasia and cancer of the oesophagus. Despite the increased use of proton pump inhibitors (PPIs) to treat reflux, the incidence of oesophageal adenocarcinoma has increased rapidly in Europe and in the United States in the last 25 years. The reasons for this increase remain unclear. In this study, we aimed to determine whether the microbiota of the gastric refluxate and oesophageal biopsies differs between patients with heartburn and normal-appeari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
155
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(176 citation statements)
references
References 39 publications
(47 reference statements)
9
155
2
3
Order By: Relevance
“…By means of nonculturing methods (i.e., quantitative PCR and 16S rRNA gene pyrosequencing), a recent study by Tsuda et al revealed very similar bacterial numbers in the gastric fluid mi-crobiota between PPI users and PPI nonusers (11). However, the PPI administration induced a small but significant increase in the intersubject diversity (11), which was consistent with previous findings by Amir et al showing an increase in the beta diversity of the gastric fluid microbiota of subjects after 8 weeks of PPI treatment (12). Furthermore, H. pylori was found to be a minor bacterium in the gastric luminal samples in the Tsuda and coworkers' study (11), whereas, as expected, the organism was identified as a dominant bacterium in gastric mucosal samples from H. pyloriinfected patients (13).…”
supporting
confidence: 83%
“…By means of nonculturing methods (i.e., quantitative PCR and 16S rRNA gene pyrosequencing), a recent study by Tsuda et al revealed very similar bacterial numbers in the gastric fluid mi-crobiota between PPI users and PPI nonusers (11). However, the PPI administration induced a small but significant increase in the intersubject diversity (11), which was consistent with previous findings by Amir et al showing an increase in the beta diversity of the gastric fluid microbiota of subjects after 8 weeks of PPI treatment (12). Furthermore, H. pylori was found to be a minor bacterium in the gastric luminal samples in the Tsuda and coworkers' study (11), whereas, as expected, the organism was identified as a dominant bacterium in gastric mucosal samples from H. pyloriinfected patients (13).…”
supporting
confidence: 83%
“…While Linsky et al found a 42 % increased risk of rCDI with PPI use during incident CDI treatment, a study by Freedberg et al found no such association, instead noting a trend for reduced rCDI with PPI therapy, consistent with reports by Rotramel and colleagues [54,58,59]. Nevertheless, PPIs have been shown to affect the gastric microbiota [60], and a small pilot study recently found that PPI use decreased the diversity of the colonic microbiota [61]; as such, the effects of PPIs on the gut microbiome and rCDI warrant further investigation.…”
Section: Recurrent C Difficile Infection (Rcdi)mentioning
confidence: 55%
“…Here, we re-analyzed a dataset by Amir and collaborators29, in order to verify whether the PC-corr method could enhance, in comparison to Amir et al 29,. our understanding of the PPI-induced microbial perturbation.…”
Section: Resultsmentioning
confidence: 99%
“…The first question of clinical relevance is whether PPIs exert any effect on the gastric bacterial communities, and this was investigated in a study by Williams and collaborators that was still solely based on culturable gastric bacteria28. More recently, next-generation-sequencing-based metagenomic studies further confirmed that PPIs modify the gastroenteric human microbiota2930313233.…”
Section: Resultsmentioning
confidence: 99%